Anticancer Activity Studies of Self-nanoemulsifying Drug Delivery Systems (SNEDDS) Hibiscus sabdariffa L. as Cisplatin Co-Chemotherapy in T47D Breast Cancer Cells - Nurma Wahyuningtyas; Laela Hayu Nurani; Nuri Ari Efiana; Nurkhasanah Nurkhasanah; Fara Azzahra; Any Guntarti; Septiana Indratmoko; Citra Ariani Edityaningrum (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Hibiscus sabdariffa L. (HS) exhibits strong anticancer activity, which can potentially treat breast cancer. A delivery system, namely self-nano-emulsifying drug delivery systems (SNEDDS), has been developed by our research group to carry the HS, indicating cytotoxicity against T47D breast cancer cells. To further evaluate the anticancer activity of HS SNEDDS, this study aimed to measure the anticancer activity of HS SNEDDS as a Cisplatin co-chemotherapy agent. The potential of HS SNEDDS as an anticancer agent was evaluated by measuring the anti-proliferation, combination index (CI), and immunocytochemistry of TNF-α gene expression. HS SNEDDS at a concentration of 241.990 µg/mL exhibited anti-proliferation properties against T47D cells with the highest doubling time, i.e., 9.4-fold compared to the control. The combination of HS SNEDDS and Cisplatin indicated a lowest CI of 0.17, showing the synergistic effect. Furthermore, combining HS SNEDDS and Cisplatin showed the highest TNF-α gene expression of 17,939 ± 7,323, indicating a better potency as a Cisplatin co-chemotherapy agent in T47D breast cancer cells compared to control and single administration. Based on these results, HS SNEDDS can be used as a co-chemotherapy agent for Cisplatin, which can increase the Cisplatin effect.